Measurement of Blood Flow and Blood Volume of the Femoral Head by Positron Emission Tomography (PET) Using C15O2 and C15O - YAMASHITA, Masato; MIZUKAWA, Norihiko; INABA, Tadashi; USHIJIMA, Yo; FURUYA, Seiichi; IDE, Mariko; ODA, Yohei; KUBO, Shunichi; NAKAHASHI, Hisamitsu (RADIOISOTOPES, 1991)
A preliminary study was carried out to evaluate whether the blood flow (F) of the femoral head can be measured by PET on the subjects (6 males, aged 54-84, mean 69.3 years) with prostate disorders (no bone lesions) . For the F study, C15O2 was inhaled in a single breath with dynamic scan for 5 minutes. The blood volume (V) was determined by the C15O study. The F (mean±1 s.d.) was 14.0±7.8 ml/100 ml [tissue] /min, the partition coefficient was 0.112±0.054, and the V was 2.23±0.56 ml/100 ml.